Étude Comparative: Sur La Competence Des Étudiants De Deuxieme Semestre De L’unnes À Écrire Le Texte Narratif En Utilisant La Serie D’images Et Le Schéma Conceptuel - Rahmadhani, Rizky Kurnia; Purwani, Neli (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2021)
CÃ¢â‚¬â„¢est une recherche comparative qui a le but de comparer la compÃƒÂ©tence des ÃƒÂ©tudiants ÃƒÂ ÃƒÂ©crire le texte narratif en utilisant deux types dÃ¢â‚¬â„¢outil de test, la sÃƒÂ©rie dÃ¢â‚¬â„¢images et leschÃƒÂ©ma conceptuel aux ÃƒÂ©tudiants de la section pÃƒÂ©dagogie du franÃƒÂ§ais de deuxiÃƒÂ¨mesemestre. CÃ¢â‚¬â„¢est une recherche descriptive quantitative dont les mÃƒÂ©thodes de la collectede donnÃƒÂ©es utilisÃƒÂ©es sont le test et la documentation. Cette recherche utilise la validitÃƒÂ©du contenu et la formule du correlationproduct-moment pour mesurer la fiabilitÃƒÂ©.LÃ¢â‚¬â„¢hypothÃƒÂ¨se de cette recherche est que la compÃƒÂ©tence des ÃƒÂ©tudiants de deuxiÃƒÂ¨mesemestre ÃƒÂ ÃƒÂ©crire le texte narratif en utilisant le schÃƒÂ©ma conceptuel est meilleure que lasÃƒÂ©rie dÃ¢â‚¬â„¢images. Les donnÃƒÂ©es obtenues sont analysÃƒÂ©es en utilisant la formule de t-test.Selon le calcul, t-calcul > t-tableau, t-calcul = 2,30, et t-tableau = 1,71. Donc, lÃ¢â‚¬â„¢hypothÃƒÂ¨seque jÃ¢â‚¬â„¢ai proposÃƒÂ©e est acceptÃƒÂ©e. Cela veut dire quÃ¢â‚¬â„¢il y a une diffÃƒÂ©rence significative dansla compÃƒÂ©tence des ÃƒÂ©tudiants de deuxiÃƒÂ¨me semestre ÃƒÂ ÃƒÂ©crire le texte narratif entre ceuxqui ÃƒÂ©crivent en utilisant la sÃƒÂ©rie dÃ¢â‚¬â„¢images et ceux qui ÃƒÂ©crivent en utilisant le schÃƒÂ©maconceptuel. This research is a comparative research aimed to compare the ability of second semester students of Frenchlanguage education program in writing narrative text using the pictures series and concept mapping. In thisresearch, the writer took the sample of second semester students of French language education program ofSemarang State University. Twenty-five students participated in this research. The subject of the test is to tellabout past activities. The research approach is a descriptive-quantitative research. The methods used to collect thedata were the writing test and the documentation. The validity of test is content validity and the product-momentcorrelation formula to measure the reliability. The data obtained is then analyzed using the t-test formula. Thecalculation showed t-counted > t-table, t-counted = 2,30, and t-table = 1,71. So the hypothesis is accepted. Itmeans that there is a significant difference between the ability of students who write narrativetext using thepicture series and students who write using the concept mapping.